Economic Networks and Urban Complementarities in the Dutch Randstad Region - Otto Raspe; Frank Van Oort; Martijn Burger (European Regional Science Association (ERSA), 2006)
In this paper we analyze the regional embeddedness of firm's networks in Dutch regions. Theorizing on urban economic networks is an important issue in the urban economic growth literature (Batten 1995, Hess 2004). For this, 2000 firms in basic sectors (industrial, business-services and wholesale) provided information on their ten most important relationships with other firms in terms of turnover. Besides the relations themselves, the type of relations (standardized, customized or joint-venture), the frequency of relations, the sectoral composition and the exact destination of relations are known. These aspects are used to create subsamples that are analyzed. We draw conclusions of the shares of intra-urban relations, intra-region relations, national relations and international relations. Aggregated to the municipal level, we test for the central place hypothesis of firms' subcontracting and delivering relations as opposed to the network hypothesis of multinodality, in six regions in the Netherlands. Conclusions on the importance of both paradigms are drawn and related to recent policy initiatives that aim at urban network development. Batten, D. (1995), "Network cities: creative urban agglomerations for the 21st Century". In: Urban Studies 32, pp. 313-327. Hess, M. (2004), "Spatial relationships? Towards a reconceptualization of embeddedness" In: Progress in Human Geography 28, pp. 165-186.
Keywords: 330